PENGUATAN MASYARAKAT DENGAN PERAN SERTA KARANG TARUNA DALAM MENINGKATKAN KUALITAS OPERASIONALISASI ORGANISASI DESA - Wely Hadi Gunawan (POLITEKNIK LP3I JAKARTA, 2022)
Karang Cadets have a vision and mission that becomes an end goal, namely improving the quality of youth resources towards anadvancement that is aligned through Karang Taruna. The development of creativity of the younger generation to establish brotherhood and a sense of togetherness becomes an organizational partner, both youth and government in the development ofcreativity and ability in the field of Social Welfare. The mission of cadet coral is to improve the quality of youth resources through Karang Taruna, Increase the social responsibility of Karang Taruna in the development of social welfare, Develop the creativity ofthe younger generation to establish brotherhood. Based on the vision and mission above, there is a big agenda whose benefits are very much awaited by the wider community, namely the work of cadet corals and has an important role in community management.However, in the direction of more community management, cadet coral brushes themselves are required to make improvements interms of organizations and institutions managed by youth. This now digital condition becomes a momentum to activate the youththrough activities that provide benefits to other communities. Community service through the involvement of cadet coral inimproving the quality of organizational management in Kuningan Regency will be one of the activation of cadet coral to improve the quality of organizational management in Kuningan Regency for example providing business institutional education needed bythe business community in the cadet coral area.Keywords : Vision And Mission, Coral Cadets, And Quality Management Of The Organization